Task Completion Detection - White, Ryen W.; Awadallah, Ahmed; Sim, Robert (Proceedings of the 42nd Annual International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR 2019), 2019)
People can record their pending tasks using to-do lists, digital assistants, and other task management software. In doing so, users of these systems face at least two challenges: (1) they must manually mark their tasks as complete, and (2) when systems proactively remind them about their pending tasks, say, via interruptive notifications, they lack information on task completion status. As a result, people may not realize the full benefits of to-do lists (since these lists can contain both completed and pending tasks) and they may be reminded about tasks they have already done (wasting time and causing frustration). In this paper, we present methods to automatically detect task completion. These inferences can be used to deprecate completed tasks and/or suppress notifications for these tasks (or for other purposes, e.g., task prioritization). Using log data from a popular digital assistant, we analyze temporal dynamics in the completion of tasks and train machine-learned models to detect completion with accuracy exceeding 80% using a variety of features (time elapsed since task creation, task content, email, notifications, user history). The findings have implications for the design of intelligent systems to help people manage their tasks.